Mining Corruption and Environmental Degradation in Indonesia: Critical Legal Issues - Hilaire Tegnan; Lego Karjoko; Jaco Barkhuizen; Anis H Bajrektarevic (BESTUUR, 2021)
Indonesia has enacted mining law, environmental protection law, and a number of rules addressing mining and environmental issues. However, the establishment of these numerous laws and regulations has not resulted in a decline in corruption cases and environmental degradation. In fact, government officials are frequently lenient with mining industry owners who fail to follow good environmental standards. This is critical since Indonesia has spent the last two decades attempting to resolve corruption and environmental challenges. This study describes specific instances of mining and environmental law confusion resulting from corrupt activities. The study takes a normative legal approach. Resources have been gathered through examinations of mining and environmental laws and regulations, as well as reports by multiple authorities that track the same subject. The study demonstrates how prior Indonesian mining law policy acknowledged regional governments as mining authorities. The policy has caused widespread mining corruption, particularly in the area of business permits, involving regional political leaders and the private sector. The irresponsibility of regional political elites has jeopardized the environment and ecosystem. It is also an echo of overlapping legislation and authorities in the mining and environmental sectors.